MORPHINE CONSUMPTION IN CANCER PATIENTS VISITING PAIN CLINIC OF TERTIARY CARE SMHS HOSPITAL: A RETROSPECTIVE OBSERVATIONAL STUDY - Dr. Arshid ahmad malik; Dr. Iram Rasool; Dr. Arshi Taj (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Morphine has been used for many years to relieve cancer pain. Oral morphine (in either immediate release or modified release form) remains the analgesic of choice for moderate or severe cancer pain. The dose of oral morphine is titrated up to achieve adequate relief from pain with minimal side effects. Aim: To assess the amount of opioid uses in cancer patients at our tertiary care unit. Methods: A profile of 30 outpatients aged ≥18 years diagnosed with cancer, who received opiod prescriptions between May 2022 and May 2023 over a period of one year at pain clinic of SMHS hospital which is one of the associated of Government Medical College Srinagar. Oral morphine equivalents (OME) were calculated using the standard conversion factors and the OME trend during the study period was assessed by a generalized additive model. Factors affecting the morphine equivalent daily dose (MEDD) were assessed using multiple linear regressions. Data were analyzed using the SPSS 21 (SPSS Inc., Chicago, IL, USA) package program. Continuous quantitative data were presented as number, mean ± standard deviation. The paired sample test was applied to non-parametric data for the statistical evaluation of repeated measurements. P<0.05 was considered significant. Results: The mean overall MEDD for all study patients was 28.9 ± 21.9 mg per day per patient. The bone and articular cartilage cancer patients had the highest MEDD. Patients with stage 4 cancer received a higher average MEDD of 5.05 (95% CI: 0.40-8.62) as compared to those with stage 1 cancer. Patients with bone metastasis received an average higher MEDD of 4.07 (95% CI: 0.72-8.19) compared to those without bone metastasis. Age was inversely associated with the MEDD. Patients aged 42-58, 59-75 and >76years old received MEDDs of 5.02 (95% CI: 3.21-8.17), 6.19 (95% CI: 4.03-8.42) and 7.89 (95% CI: 7.05-12.01) compared with those aged 18-42 years old. Brain metastasis was inversely associated with MEDD of 5.21 (95% CI: 1.01-8.39) compared to those without brain metastasis. Conclusion:Oral morphine use has increased over time in Kashmir but remains substantially lower than estimated need. Opioid use in cancer patients in this study was lower than the average global usage. There is significant geographic variation of use. Efforts are needed to improve palliative care in Kashmir and to reduce regional disparities in access to opioids.